Using Instagram as a Promotional Media to Build Brand Awareness in Mushroom Kaliraya MSMEs - Indiana, Widya (Proceeding Kilisuci International Conference on Economic & Business, 2024)
Research aim: The aim of this research is to determine the use of Instagram as a strategy in building brand awareness of Mushroom Kaliraya MSMEs. Design/Method/Approach: This research uses a qualitative approach with qualitative approach analysis techniques carried out using a reduction process. Data collection techniques in this research were carried out by means of interviews, observation and documentation. Research Finding: That by implementing promotions using Instagram carried out by UMKM Mushroom Kaliraya , they have utilized the features on Instagram such as photo and video features, comments for interaction, captions for messages, and location, hashtags to help disseminate information and also increase feedback, as well as involves four elements of the marketing mix (product, price, place, promotion) which are factors in influencing brand awareness so that it gives a good impression in the minds of consumers which is formed as a local brand that is easily accessible. Research limitation: Lack of observation means not being able to gather information about promotional strategies. This limits the research's ability to provide in-depth insights. In further research, it is hoped that new problems can be discovered.